Dosimetric comparison of robotic- and LINAC-based treatment of spine stereotactic body radiotherapy - Acar, Hilal; Yazıcı, Ömer; Ünal, Dilek (Elsevier Inc., 2022)
To determine which treatment technique and modality would offer better dosimetric results and be preferable for spinal stereotactic body therapy (SBRT) depending on the three different regions of the vertebrae. Linear accelerator (LINAC)- and CyberKnife (CK)-based treatment techniques were compared in terms of their dosimetric quality, treatment efficiency, and delivery accuracy. Thirty previously treated patients were included in this study. Intensity-modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) techniques were used for LINAC-based treatment, whereas CK-based treatment plans were generated for two different collimator systems: fixed and multileaf collimator (MLC). The plans were compared based on spinal cord sparing, dose homogeneity, conformity index (CI), gradient index (GI), monitor unit (MU), and beam-on time. The percentage volumes of V2Gy, V5Gy (representing volume low of the dose spillage region), V10Gy, and V20Gy (representing the volume of the high-dose spillage region) of the healthy tissue were analyzed. The CI and GI of the VMAT plans were better than those of the IMRT plans. For spinal cord sparing, the VMAT and MLC-based CK (CK-MLC) techniques were superior. The percentage of low-dose spillage regions was the lowest for IMRT and fixed cone-based CK (CK-FIX) plans. The percentage of the high-dose spillage region was the lowest for the VMAT and CK-MLC plans. In terms of treatment efficiency, the VMAT and CK-MLC plans were superior to the IMRT and CK-FIX plans. The VMAT technique lowered the MU and beam-on time values. The plan delivery accuracy of the VMAT and CK-FIX plans was better than that of the IMRT plans. VMAT is the best option for LINAC-based spinal SBRT. For CK-based spinal SBRT, MLC-based plans are preferred. If the clinic has both treatment modalities and the patient can tolerate long treatment times, CK-MLC-based treatment should be chosen because of its superiority in sparing the spinal cord and sharp dose fall-off.
Keywords: Cyberknife; FIX Cone; IMRT; MLC; Spine SBRT; VMAT